TANGGUNG JAWAB PENGAWASAN PEMERINTAH DALAM MELINDUNGI HUTAN PRODUKSI TERBATAS MAPONGKA DI KABUPATEN TANA TORAJA - Aulia Faradiba Tilameo; Sri Susyanti Nur; Kahar Lahae (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2022)
Abstract This study aims to formulate, identify, and analyze the type of provincial government oversight necessary to safeguard the Mapongka Limited Production Forest (HPT) in Tana Toraja Regency, as well as the barriers that prevent the provincial government from keeping an eye on and reining in forest encroachment there. By gathering primary data in the form of interviews and secondary data obtained through literature study, this type of research discusses the manner in which the provincial government supervises itself as well as the barriers that prevent it from keeping an eye on and reining in forest squatters in the Tana Toraja Regency's Mapongka Limited Production Forest Area (HPT). The collected data were then subjected to qualitative analysis. The findings of this study suggest that (1) forestry authorities are in charge of supervision. Special police powers are granted to some officials. (1) Obstacles that prevent the provincial government from monitoring and controlling forest encroachers in the Mapongka Limited Production Forest Area (HPT) of Tana Toraja Regency because of a lack of personnel/HR UPT Saddang I Forest Management Unit, inadequate infrastructure, and a lack of public awareness of the importance of controlling forest encroachment are covered by the authority of the forestry police. Keywords: Forest with little production, Government, Responsibility.